The tourism knowledge system. (March 2016) - Tribe, John; Liburd, Janne J.
Highlights: This conceptual study presents a tourism knowledge system. It synthesises, discards, re-orders and adds material to the previous literature. Analyses the structure, systems, processes and outcomes of tourism knowledge. Examines the space, force-field, networks and production of knowledge. Key challenges and consequences of the knowledge system are discussed. Abstract: This conceptual study addresses the significant need for every mature field of knowledge to understand itself. It builds upon previous studies of the epistemology and ontology of tourism by critiquing, synthesising, discarding, re-ordering and adding material. Its contribution is an original reconceptualisation of the structure, systems, processes and outcomes that define the field of tourism. These are explained by the creation of a model and detailed analysis that examines knowledge space, the knowledge force-field, knowledge networks, four key domains in knowledge creation and their interrelationships. Finally the model is used to examine some of the key challenges and consequences that the knowledge system reveals for tourism and its research.